The inhibition of circular RNA circNOLC1 by propofol/STAT3 attenuates breast cancer stem cells function via miR-365a-3p/STAT3 signaling - Yi-Ping Liu (BMC, 2021)
Abstract Background Breast cancer remains one of the most dreadful female malignancies globally, in which cancer stem cells (CSCs) play crucial functions. Circular RNAs have drawn great attention in cancer research area and propofol is a widely applied intravenous anesthetic agent. Methods: In the current study, we explored the function of circular RNA nucleolar and coiled-body phosphoprotein 1 (circNOLC1) in CSCs of breast cancer and the inhibitory impact of propofol on circNOLC1. Results The expression of circNOLC1 was induced in breast cancer tissues compared with the non-tumor tissues. The silencing of circNOLC1 was able to repress the viability of breast cancer cells. Meanwhile, the numbers of colony formation were suppressed by circNOLC1 knockdown in breast cancer cells. The inhibition of circNOLC1 reduced the invasion and migration ability of breast cancer cells. The mRNA and protein levels of E-cadherin were enhanced but Vimentin levels were reduced by the silencing of circNOLC1. The repression of circNOLC1 decreased the side population (SP) ratio in breast cancer cells. Meanwhile, the sphere formation ability of breast cancer cells was attenuated by the silencing of circNOLC1. The levels of ATP-binding cassette (ABC) superfamily G member 2 (ABCG2), c-Myc, B cell-specific Moloney murine leukemia virus integration site 1 (Bmi1), and SRY-box transcription factor 2 (Sox2) were repressed by the depletion of circNOLC1 in the cells. Regarding to the mechanism, circNOLC1 functioned as a competing endogenous RNAs (ceRNAs) for microRNA-365a-3p (miR-365a-3p) and the inhibition of miR-365a-3p rescued circNOLC1 depletion-repressed proliferation and cancer stem cell activity of breast cancer. MiR-365a-3p targeted signal transducer and activator of transcription 3 (STAT3) in breast cancer cells and circNOLC1 enhanced STAT3 expression by sponging miR-365a-3p. The overexpression of STAT3 could reverse miR-365a-3p or circNOLC1 depletion-inhibited proliferation and cancer stem cell properties of breast cancer. Interestingly, the expression of circNOLC1 and STAT3 was repressed by the treatment of propofol. The enrichment of STAT3 on circNOLC1 promoter was inhibited by propofol. The expression of circNOLC1 was suppressed by the silencing of STAT3 in the cells. The inhibition of circNOLC1 expression by propofol was rescued under the co-treatment of STAT3 overexpression. The overexpression of circNOLC1 rescued propofol-attenuated proliferation and cancer stem cell functions in vitro and in vivo. Conclusions Thus, we concluded that circNOLC1 contributes to CSCs properties and progression of breast cancer by targeting miR-365a-3p /STAT3 axis and propofol inhibited circNOLC1 by repressing STAT3 in a feedback mechanism.